The Effects of Promotional Media and Service Quality on Customers’ Savings Intention at PT Bank Sumut Head Office, Medan - Asri Rahma Zalukhu; Maduma Sari Sagala; Siswanto Siswanto (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: In the current digital era, banks must implement effective marketing strategies to attract public interest in savings. Promotional media and service quality are two critical factors influencing customer savings decisions. This research aims to analyze the influence of promotional media and service quality on savings interest at PT. Bank Sumut Head Office in Medan City, both partially and simultaneously. Materials and methods: This quantitative research involved 92 registered customers in 2024. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS Version 25. Results: The regression analysis yielded Y = 5.065 + 0.305X₁ + 0.543X₂ + e, indicating that promotional media and service quality positively influence savings interest. The t-test showed that promotional media (t-count = 3.344 > t-table 1.986, sig. 0.001 < 0.05) and service quality (t-count = 5.731 > t-table 1.986, sig. 0.000 < 0.05) have significant positive effects on savings interest. The F-test (F-count = 85.096 > F-table 3.10) confirmed a simultaneous positive influence. The coefficient of determination (R²) was 0.649 (64.9%), indicating that promotional media and service quality explain 64.9% of the variance in savings interest, while 35.1% is influenced by other factors. Conclusions: Both promotional media and service quality significantly and positively influence savings interest at PT. Bank Sumut. Banks should enhance digital promotional strategies and maintain high service quality to increase customer savings interest and loyalty.